In defense of phenomenological approaches to communication studies: an intellectual history. Issue 1 (2nd January 2018) - Sturgess, Jessica N.
ABSTRACT: This essay offers an intellectual history of the emergence of phenomenological philosophy in the field of communication studies. The essay traces the early contours of phenomenology both in Continental Europe and in its immigration to the U.S.A., in each scenario mapping its conceptual offerings to theorizing communication. Upon doing so, the essay turns to the historical integration of phenomenology into communication departments by tracking figures in the field from its inception through its contemporary instantiation. The essay concludes by offering justification for the continued relationship between phenomenology and communication studies as it offers a fruitful approach to communicative research.